Diagnosing Frontal Dynamics From Observations Using a Variational Approach. Issue 11 (27th October 2022) - Cutolo, Eugenio; Pascual, Ananda; Ruiz, Simón; Shaun Johnston, T. M.; Freilich, Mara; Mahadevan, Amala; Shcherbina, Andrey; Poulain, Pierre‐Marie; Ozgokmen, Tamay; Centurioni, Luca R.; Rudnick, Daniel L.; D'Asaro, Eric
Abstract: Intensive hydrographic and horizontal velocity measurements collected in the Alboran Sea enabled us to diagnose the three‐dimensional dynamics of a frontal system. The sampled domain was characterized by a 40 km diameter anticyclonic eddy, with an intense front on its eastern side, separating the Atlantic and Mediterranean waters. Here, we implemented a multi‐variate variational analysis (VA) to reconstruct the hydrographic fields, combining the 1‐km horizontal resolution of the Underway Conductivity‐Temperature‐Depth (CTD) system with information on the flow shape from the Acoustic Doppler Current Profiler velocities. One advantage of the VA is given by the physical constraint, which preserves fine‐scale gradients better than the classical optimal interpolation (OI). A comparison between real drifter trajectories and virtual particles advected in the mapping quantified the improvements in the VA over the OI, with a 15% larger skill score. Quasi‐geostrophic (QG) and semi‐geostrophic (SG) omega equations enabled us to estimate the vertical velocity ( w ) which reached 40 m/day on the dense side of the front. How nutrients and other passive tracers leave the mixed‐layer and subduct is estimated with 3D advection from the VA, which agreed with biological sampling from traditional CTD casts at two eddy locations. Downwelling warm filaments are further evidence of subduction, in line with the w from SG, but not with QG. SG better accounted for the along‐isopycnal component of w in agreement with another analysis made on isopycnal coordinates. The multi‐platform approach of this work and the use of variational methods improved the characterization and understanding of (sub)‐mesoscale frontal dynamics. Plain Language Summary: Ocean water currents move mainly horizontally, while the vertical velocity is pretty slow and thus hard to measure. However, despite its small magnitude, vertical exchange from the ocean surface to its interior is relevant for climate change (e.g., carbon distribution and export) and contaminant dispersal. In this work, we first reconstruct the small features of the ocean combining the measurements of the water velocity with its hydrographic properties like salinity and temperature. From this reconstruction we estimated and characterized the vertical velocity in a frontal region. This estimation was possible through repetitive measurements carried on by a research vessel in the Alboran Sea and led to a magnitude of 40 m/day. We confirmed our estimations with independent observations of drifting buoys and nutrients sampling which followed 2D and 3D trajectories in agreement with our velocity fields. Key Points: Combining velocity and hydrographic observations with a thermal‐wind based constraint, variational analysis reconstructs small‐scale frontal features Frontal vertical velocity computed through semi‐geostrophy reaches 35 m/day and explains the subduction of nutrients and warm water filaments Along‐isopycnal component of the vertical velocity explains 60% of its total magnitude at the front